“THE INFLUENCE OF UNCONVENTIONAL BRAND NAME SPELLING: CONSUMER BEHAVIOR AND MARKETING IMPLICATIONS” (REVIEWING HOW UNCONVENTIONAL BRAND NAME SPELLINGS INFLUENCE CONSUMER DECISION MAKING AND BRANDING) - Anggun Yolistina; Nida Garnida Fitrianti; Raden Roro Fatmasari (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
The use of unconventional brand name spellings has become an increasingly popular strategy in modern marketing to differentiate a brand from its competitors. However, its impact on consumer perception, brand identity and emotional connection is still not fully understood. This article investigates how marketing strategies can be adapted to capitalize on or reduce the impact of using unconventional brand name spellings in building a strong brand identity and creating an emotional connection with consumers. Through a literature review and in-depth analysis, we explore the role of culture, language, and demographic characteristics in responding to unconventional spelling. We also identified marketing strategies that can be implemented to capitalize on or reduce the impact of using unconventional brand name spellings, including creative approaches to brand design, building a strong brand narrative, and a deep understanding of the target market and consumers. The results show that the use of unconventional spelling can be an effective tool in building a unique brand identity and creating an emotional connection with consumers, especially if supported by the right marketing strategy. However, it is important to consider cultural, demographic and linguistic context to avoid the risk of negative perceptions or consumer confusion. In conclusion, the use of unconventional brand name spellings can be a powerful strategy in modern marketing, but it requires a careful approach tailored to the market and consumer context to achieve optimal results.